Gambaran Kestabilan MAP (Mean Arterial Pressure) dan Heart Rate Pasien Spinal Anestesi Di RSUD dr. R. Goeteng Taroenadibrata Purbalingga (PROFESSIONAL HEALTH JOURNAL, 2024)
Giving spinal anesthesia has advantages such as reducing the risk of acute complications which often occur, namely blood pressure instability in the form of a decrease in blood pressure or hypotension. Appropriate and rapid action to reduce blood pressure after administering spinal anesthesia must be taken to avoid complications. Hemodynamic changes occur due to sympathetic vasomotor blockade due to spinal anesthesia. The aim of this research is to determine the stability of Mean Arterial Pressure and heart rate in spinal anesthesia patients at RSUD dr. R Goeteng Taroenadibrata Purbalingga. The type of research carried out is quantitative research with a descriptive design. The approach used during the research was cross sectional. The sampling technique used purposive sampling for 64 patients. The measuring instruments used are a bedsite monitor scale and an observation sheet. Data analysis used univariate tests in the form of frequency distribution tables. The research results showed that the average age was 51.77 years and the most dominant gender was female (53.1%). Most of them had no history of disease (71.9%). Description of the stability of Mean Arterial Pressure in spinal anesthesia patients with an average MAP of 96.16. The heart rate of spinal anesthesia patients was an average of 79.06 beats per minute.